The Effect of Olive Oil Addition into Oatmeal in Lowering Total Blood Cholesterol and LDL (Low Density Lipoprotein) in Wistar Rat - Sebastian Hadinata; Heddy Herdiman; Fenny Tanuwijaya (Universitas Kristen Maranatha, 2016)
Oat contains beta-glucan fiber and olive oil contains unsaturated fatty acids which havebeen proven to decrease blood cholesterol. This research compared the effect between acombination of oatmeal and olive oil and each food as single intake in decreasing total bloodcholesterol and LDL cholesterol. We used 25 rats (Rattus norvegicus L.), divided them into fivegroups; negative control (KN), positive control (KP), olive oil group (KMZ), oatmeal group(KBG), and combination group (KMZ+KBG). The total blood cholesterol and LDL cholesterollevels were measured after 14 days of induction and after 28 days of treatment. Data wereanalyzed using one way ANOVA, continued with LSD test with Î± = 0.05. The result showedthere were 10.85%, 8.85% and 6.60% lower in total blood cholesterol level using KMZ+KBG,KMZ and KBG respectively and 13.85%, 9.33% ,and 8.80% lower in LDL cholesterol levelusing KMZ+KBG, KMZ and KBG respectively. ANOVA test showed a significant decrease ineach treatment. LSD test showed that there was a significant difference between KMZ+KBGcompared to KBG in total blood cholesterol and LDL lowering, but did not showed significantdifference compared to KMZ.Keywords: oatmeal, olive oil, total blood cholesterol, LDL